Beauty Clinic Information Systems Based on Android - Hidayati, Anita; Rahayu, Widiatama (MULTINETICS, 2019)
As the times progressed, the world of beauty seemed to expand quite rapidly. Beauty clinics are increasingly emerging like Esthedica Clinic Face and Body Treatments. However, information on the clinic Esthedica still somewhat less for the customer. This can be seen from the customers who always ask about the details of treatment, doctor's schedule, and promotion at the clinic. Not infrequently customers also have to wait long to perform treatment or counseling because of the queue of patients that are sometimes quite a lot. This affects the customer relationship that may feel the lack of convenience provided by the clinic to the customer. Customers also find it difficult to get clinical information that they usually get through telephones and chat apps that are personal and not uncommon too slow response. Therefore, the authors make the application of information systems based on the android beauty clinic Esthedica Face and Body Treatments using GRAPPLE (Guideliness for Rapid Application Engineering) method. In this thesis android based applications will be built to provide information on the Esthedica clinic that is information on various treatments available at the clinic, doctor schedule information, and clinic promotion. Through this application also customers can make booking treatment or consultation with a doctor.